Multiscale modeling: Physiome project standards, tools, and databases - Hunter, P; Li, W; McCulloch, A; Noble, D (2006)
The Physiome Project's markup languages and associated tools leverage the CellML and FieldML model databases published in peer-reviewed journals. As these tools mature, researchers can check models for conformance to underlying physics laws, using them to develop complex physiological models from separately validated components. © 2006 IEEE.